REKONSTRUKSI SEBAGAI UPAYA MENGUNGKAP TINDAK PIDANA PEMBUNUHAN BERENCANA (Studi Kasus Wilayah Hukum Polsek Banyumanik Semarang) - Wahyu Sudrajad; Umar Ma’ruf (Jurnal Hukum Khaira Ummah, 2019)
The number of criminal acts committed by the community, especially the criminal act of murder, made the police officers investigators to conduct investigations. In particular Criminal Acts Murder crime requires the use of evidence or some kind of other guidance commonly referred to as the reconstruction of criminal acts, this makes the author want to know how the reconstruction as an effort to uncover the crime of murder planning case study of banyumanik polsek semarang law. The issues raised are what is the implementation of the reconstruction in an effort to uncover the crime of premeditated murder, what are the necessary reconstruction in an effort to reveal the crime of premeditated murder, what kind of criminal law policy in Indonesia in the field of reconstruction in an effort to reveal the crime of premeditated murder in the future come.The method used by the authors in making this thesis is the method of sociological juridical approach, namely by conducting interviews and perform data collection both from primary data and secondary data.According to the results of the authors' research, the implementation of the reconstruction is regulated in the Attachment to Decree of the Chief of Police. Pol: Skep 1205 / 1X / 2000 on the Revision of the Juklak and Juknis Association The Criminal Investigation Process has mentioned the implementation of reconstruction and what the reconstruction needs, the criminal law policy on reconstruction that is Indonesia must make revamping both substantial improvements namely improvements in terms of legislation - an invitation by establishing and drafting specific legislation concerning the investigative body in Indonesia.Keywords: Reconstruction, Killing, Banyumanik Polsek.